Analysis of the non-pitch middle ground of the functioning of light industry enterprises from the position of a marketing approach - ASAMOAH-KYEREMEH, Joshua; MATIUKH, Sergii (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article identifies the main trends in the development of light industry in Ukraine in a historical context. It has been reported that behind the development of globalization processes, the center for the production of clothing, and other goods in widespread use, has moved to the extremes of Western and Central Asia, Western America. The current business environment of the country was analyzed and changes were made to the main macroeconomic indicators of the development of the Ukrainian economy. When forming a significant number of light ratings for 2023, the development of the Ukrainian economy will not be considered important for military activities on its territory. Due to the development of the light industry sector, until 2022 it was actively developing and formed almost 1 hundred percent of the region’s industrial production industry. It has been established that, regardless of the popular mind, light industry enterprises have been gradually increasing their sales obligations since 2010. Period 2010-2021 Characteristic: development of distribution channels, online trading; more active use of marketing tools for the distribution of goods from the agricultural sector; branding. The COVID-19 pandemic and quarantine brought about a surge in digital marketing tools, which led to increased trade. It has been established that the core of the functioning of light industry enterprises is characterized by the presence of fierce competition, the need to react quickly to changes in the market situation, the presence of external a threat to ensuring competitive advantages, which necessitates the need for a variety of marketing tools for the development of government entities and the provision of their economic security.